Is personality linked to season of birth? - Hoseon Lee (Public Library of Science (PLoS), 2021)
The environment is a very significant factor in early childhood development. Season of birth (SOB) is a proxy viable for the environment to which the babies are exposed, thus also significant in early development. This study investigates the association between SOB and personality. A total 2,962 college students were included as study participants. The participants were classified into four seasonal groups based on their birth month and underwent a personality assessment using the Temperament and Character Inventory (TCI). Statistical analysis was performed using one-way analysis of variance (ANOVA) and multinomial logistic regression analysis. The male participants born in autumn scored high on the Disorderliness (NS4) subscale (β = 0.055, P = 0.042) and the male participants born in summer and winter scored high on the Extravagance (NS3) subscale (summer: β = 0.072, P = 0.01, winter: β = 0.078, P = 0.003). The difference observed indicates a relationship between the SOB and temperament, especially NS. Our findings suggest that environmental factors may affect temperament in early development, although further research is likely needed to clarify the causality between them.